Balancing autonomy and care: The ethical and legal dilemmas of artificial nutrition and hydration under compulsory health treatment - Karaboue, Karidia; Lacasella, Giorgia Viola; Karaboue, Michele Ahmed Antonio (Progress in Nutrition, 2025)
The complex issue of informed consent in the context of administering Artificial Nutrition and Hydration (ANH) under Compulsory Health Treatment (TSO) is explored, examining whether ANH can be forcibly administered, particularly in cases involving patients with eating disorders such as severe anorexia. The tension between respecting patient autonomy and the medical duty to provide care, especially when the patient cannot give valid consent, is highlighted. While TSO represents a significant limitation on personal freedom, it must be justified only under extreme clinical conditions, with the patient’s informed consent being paramount whenever possible. Advocacy for a therapeutic alliance and empathetic-supportive approach is emphasized, stressing the importance of non-coercive methods and respecting patient self-determination. Additionally, a multidisciplinary approach in decision-making is underscored, involving ethicists, legal experts, and family members to ensure that decisions align with the patient’s best interests and uphold their dignity and autonomy.